Friction and wear of polypropylene-based composites reinforced with cherry seed powder. (January 2023) - Wojciechowski, Ł.; Sydow, Z.; Bula, K.; Gapiński, B.
Abstract: Waste management is one of the most important challenges for humanity in the 21st century. The application of waste materials to reinforce metal and polymer composites could be one way to keep them the circular economy loop for as long as possible and follow the 3 R approach: reduce, reuse and recycle. Following this principle, in this article we propose the use of cherry seed filler to strengthen polypropylene-based composites for tribological applications. For the production of the composite, a filler made of cherry seed powder of various percentages (5 %, 10 % and 15 %) and granulation (d < 400 µm, 400 < d < 630 µm, and 630 < d < 800 µm) was used. The prepared materials were subjected to tribological tests (under dry friction conditions) in the "block-on-ring" system (where the blocks were made of composite materials and the rings were made of AISI 1045 steel). The frictional behaviour was analysed on the basis of the measured values of the friction torque and the coefficient of friction calculated from it (and the applied load). For statistical purposes, the tests were repeated four times for each sample configuration. The mean values of the friction torque and the coefficient of friction were used in the discussion of the results. The wear mechanisms and the level of wear were identified on the basis of the authors' interpretation of the SEM and EDS investigations and the results of the topographic measurements.